2012
DOI: 10.1016/j.nuclphysb.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational actions in two dimensions and the Mabuchi functional

Abstract: The Mabuchi energy is an interesting geometric functional on the space of Kähler metrics that plays a crucial rôle in the study of the geometry of Kähler manifolds. We show that this functional, as well as other related geometric actions, contribute to the effective gravitational action when a massive scalar field is coupled to gravity in two dimensions in a small mass expansion. This yields new theories of two-dimensional quantum gravity generalizing the standard Liouville models.October 26, 2018 † On leave o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(92 citation statements)
references
References 23 publications
3
89
0
Order By: Relevance
“…Similar transformation laws were studied in [7] in two dimensions and the above relations can be proved by using similar methods.…”
Section: The Weyl Transformation Of the Green Functionsmentioning
confidence: 81%
See 2 more Smart Citations
“…Similar transformation laws were studied in [7] in two dimensions and the above relations can be proved by using similar methods.…”
Section: The Weyl Transformation Of the Green Functionsmentioning
confidence: 81%
“…Recently, a non-perturbative definition of the path integral over the Kähler metrics on a compact complex manifold of arbitrary dimension was proposed in [6] (see also [7,8] for related works). The main ingredient in the construction of the path integral is to approximate the infinite dimensional space of Kähler metrics M at fixed Kähler class by finite dimensional subspaces M n of so-called Bergman metrics.…”
Section: A Note On Some Of Our Original Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mathematical literature they appear in relation with the characterization of constant scalar curvature metrics. Their roles as two-dimensional gravitational actions in the sense of (1.1) have been put forward in [6]. In particuler, ref.…”
Section: Jhep11(2017)154mentioning
confidence: 99%
“…[6] has studied the metric dependence of the partition function of non-conformal massive matter on compact Riemann surfaces and shown that a gravitational action defined by (1.1) contains these Mabuchi and Aubin-Yau actions as first-order corrections (first order in m 2 A where m is the mass and A the area of the Riemann surface) to the Liouville action. The study of [6] was further confirmed and generalized in [7] where an exact formula for the gravitational action for any value of the mass was obtained, its expansion in m 2 A giving back the results of [6]. The Mabuchi action has drawn much attention in recent years.…”
Section: Jhep11(2017)154mentioning
confidence: 99%